Serum sphingosine negatively correlates with albumin predicting the risk of hepatocellular carcinoma - Huang, Kai; Li, Wanlian; Xiao, Juan; Luo, Diteng; Jin, Junfei (Biomedical papers, 2020)
Background: The roles of sphingosine in various cancers have not been fully investigated. Our aim was to identify the relationship between serum sphingosine and the risk of hepatocellular carcinoma (HCC). Methods: Serum sphingosine in 34 normal people and 73 HCC patients were reviewed retrospectively. Receiver operating characteristic curve analysis was performed to determine the cut-off values of sphingosine in the serum. Chi-square test, t test and regression analysis were used to test the association between serum sphingosine and individual clinicopathologic parameters. Results: Serum sphingosine was higher in HCC patients (155.91 extpm331.5 ng/mL) with normal persons as the control (30.92 extpm29.4 ng/mL). The sphingosine threshold according to ROC curve was set at 22.5 ng/mL with a sensitivity of 74%, and a specificity of 55.9%. Meanwhile, sphingosine in HCC patients with abnormal albumin was significantly higher than that in patients with normal albumin (t=2.452, P=0.019). When HCC patients were divided into two groups serum sphingosine was negatively associated with albumin in HCC patients (χ2=4.469, P=0.035). Moreover, the logistic regression analysis showed that large tumor size (P=0.018, OR=0.13) and a low albumin (P=0.005, OR=8.856) were two independent risk factors for serum sphingosine upregulation. High AFP coupled with high serum sphingosine, high sphingosine and high AFP respectively were found in 91.2%, 75.4%, 73% of the HCC patients. Conclusions: These results suggest that serum sphingosine could be treated as a marker for the risk of HCC. AFP and sphingosine in the serum could be used together for HCC diagnosis.
Keywords: serum sphingolipid; HCC; albumin